Speed tracer / Muhamad Alif Alias & Mohd Ashraf Mohamad - Alias, Muhamad Alif; Mohamad, Mohd Ashraf (2015)
The focus of this project are for the transporter like bus and lorry with the bigger size of vehicle in the road, with is to detect the speed besides tracking the coordinate. Mostly, the biggest transport like we discuss are cause accident with high rate of victim. It also having high rate of casualties depend on other accident. Therefore we built this speed tracer in term of to know the speed we also can know the coordinate of the vehicle. This speed tracer device is both hardware and software integrated into a device which will be an alternative for authorities who cannot investigate the cause of accident. The main focus is on this problems faced by Authorities to investigate, tracking, and detect the speed of vehicle from before accident happen, we also can prevent the accident before it happened. Whenever the authorities went to detect traffic problem they have to use these device to know the positioning and speed of transport. A GPS system is used by the device/hardware to transmit and receive the data in term of longitude, latitude, time and date it happen when the transport start moving. If we use GSM system the data will be send a notification to the Authorities compute ring system whenever the vehicle are moving in high speed and over limit. The Authorities can do enforcement for offender traffic. This system are limited for authorities to detect the transporter who has offense of law of traffic. Based on this project, speed tracer are importance to do traffic enforcement in our country. Unfortunately, we might got one problem there is Arduino Uno R3 coding storage problem. We cannot complete our program to making our project functioning well.